Skin manifestations of neuroendocrine neoplasms: review of the literature - Walecka, Irena; Owczarek, Witold; Ciechanowicz, Piotr; Dopytalska, Klaudia; Furmanek, Mariusz; Szczerba, Michał; Walecki, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Neuroendocrine neoplasms (NENs) are a heterogeneous group of rare tumours derived from peptidergic neurons and specialized neuroendocrine cells capable of secreting various peptides or amines. These cells may be present in endocrine tissue or diffused in the tissues of the digestive or respiratory system. The article reviews the characteristic features of NENs, with particular emphasis on skin manifestations, such as necrolytic migratory erythema (NME), tongue inflammation, angular cheilitis, venous thrombosis and alopecia in glucagonoma; “flushing”, “lion face”, pellagra skin symptoms, “scleroderma-like features without Raynaud’s phenomenon” in carcinoid tumours. The paper also presents the clinical picture of the neuroendocrine tumour of the skin – Merkel cell carcinoma. The aim of this study was to draw attention to the need for precise and comprehensive diagnosis of the patients, with particular emphasis on skin lesions as a revelator of neuroendocrine tumours. This management allows for the early implementation of appropriate treatment.